Single-cell dynamics of pannexin-1-facilitated programmed ATP loss during apoptosis - Hiromi Imamura; Shuichiro Sakamoto; Tomoki Yoshida; Yusuke Matsui; Silvia Penuela; Dale W Laird; Shin Mizukami; Kazuya Kikuchi; Akira Kakizuka (eLife, 2020)
ATP is essential for all living cells. However, how dead cells lose ATP has not been well investigated. In this study, we developed new FRET biosensors for dual imaging of intracellular ATP level and caspase-3 activity in single apoptotic cultured human cells. We show that the cytosolic ATP level starts to decrease immediately after the activation of caspase-3, and this process is completed typically within 2 hr. The ATP decrease was facilitated by caspase-dependent cleavage of the plasma membrane channel pannexin-1, indicating that the intracellular decrease of the apoptotic cell is a ‘programmed’ process. Apoptotic cells deficient of pannexin-1 sustained the ability to produce ATP through glycolysis and to consume ATP, and did not stop wasting glucose much longer period than normal apoptotic cells. Thus, the pannexin-1 plays a role in arresting the metabolic activity of dead apoptotic cells, most likely through facilitating the loss of intracellular ATP.